"Wishes Unknown: " A Case Report. Issue 5 (1st September 2019) - Perez-Protto, Silvia E.; Rowbottom, James R.; Taylor, Mark A.
Abstract : We report the case of a 55-year-old woman who required extracorporeal membrane oxygenation for extreme respiratory distress after a liver transplant and eventually died. As is so often the case, this patient's values and wishes were not documented before she had a risky surgical procedure. Anesthesiologists, in partnership with surgeons, can participate in preoperative discussions exploring wishes and values and document them in advance directives which will help clinicians respect patients' preferences.